2018
DOI: 10.3389/fpsyt.2018.00133
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Psychiatric Disorders in Allergic Diseases: A Nationwide, Population-Based, Cohort Study

Abstract: Background/objectiveAllergic diseases, such as bronchial asthma, allergic rhinitis, atopic dermatitis, and psychiatric disorders, are major health issues. There have been reports that allergic diseases were associated with depression or anxiety disorders. This study aimed to investigate the association between these allergic diseases and the risk of developing overall psychiatric disorders in patients from Taiwan.MethodsThis cohort study used the database of the Taiwan National Health Insurance Program. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 96 publications
2
47
0
3
Order By: Relevance
“…Consistent with one prior study [ 29 ], our main analysis showed no significant association between seasonal allergies and alcohol or substance use disorders. To our knowledge, this study is one of the few studies that has examined seasonal allergies and eating disorders [ 49 ], and potentially the only study to have done so in the United States. We found that seasonal allergies were associated with a greater risk for eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with one prior study [ 29 ], our main analysis showed no significant association between seasonal allergies and alcohol or substance use disorders. To our knowledge, this study is one of the few studies that has examined seasonal allergies and eating disorders [ 49 ], and potentially the only study to have done so in the United States. We found that seasonal allergies were associated with a greater risk for eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations that warrant consideration. First, similar to previous studies using the NHIRD on infectious, parasitic, or inflammatory diseases [57][58][59][60][61] , since the severity, weakness severity, laboratory parameters, or lung function examinations in SARS patients were not recorded in the NHIRD. Second, other factors, such as genetic, psychosocial, and environmental factors, were not included in the dataset.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…The enrolled participants exceeded 99% of the population and were contracted with 97% of the medical providers (Ho Chan, 2010). The details of this program have been documented in previous studies (Huang et al, 2014;Tang et al, 2015;Yang et al, 2015a;Tzeng et al, 2016;Tzeng et al, 2017a;Tzeng et al, 2017c;Chao et al, 2018;Chu et al, 2018;Tzeng et al, 2018;Tzeng et al, 2019b). The data sources of the present study were two million randomly sampled patients from the Longitudinal Health Insurance Database (LHID), a subset of the NHIRD, over a 15-year period (2000NHIRD, over a 15-year period ( -2015.…”
Section: Data Sourcesmentioning
confidence: 99%